The work of farmers in short food supply chains: Systematic literature review and research agenda - Philippine Dupé; Benoît Dedieu; Pierre Gasselin; Guillaume Ollivier (PLoS ONE, 2025)
Background Over the last 20 years or so, farmers the world over have been expressing renewed interest in Short Food Supply Chains (SFSCs). Since these marketing channels bring consumers and producers closer together, they are being promoted as a means for producers to recover more of the added value. They are also seen as a part of the solution to the problems associated with long supply chains. However, marketing via SFSCs means that farmers have to take on new tasks, which are likely to disrupt their existing work routines. We propose here to review the scientific knowledge available on the work of farmers in SFSCs. Methods We carry out a systematic analysis of the English-language literature using a multidisciplinary analytical framework of work. We consider five dimensions of work: 1) structural elements of work; 2) economic performance of work; 3) organization of work; 4) working conditions; and 5) occupation. Results The theme of work is not prominent in the existing literature on SFSCs. While there is ongoing debate whether a switch to SFSCs results in increased farm incomes, it is clear that marketing through SFSCs relies on a large amount of poorly remunerated work. New tasks have to be added to work schedules, and new skills are required, making the organization of both productive and marketing work more complex. Various categories of workers are involved in undertaking these tasks, having to bear a heavy workload that is a source of stress and fatigue. However, the economic aspect aside, SFSCs appear to be conducive to farmers’ self-fulfillment at work. Farmers derive particular satisfaction from their involvement in SFSCs since they are more in touch with consumers and because they are participating in the transition of food systems, despite the intellectually and physically demanding work they have to do. Conclusion We call for the study of farmers’ work in SFSCs to be strengthened, by diversifying both the methodologies adopted and the case studies. Such knowledge should enable us to better integrate work-related issues into future public policies to support SFSCs.